Themes in the Indonesian Discourse on Educational Philosophy: A Systematic Review - Sulastri Sulastri; Mike Atnelie; Lelaini Lelaini; Tri Muryanti; Gusti Anggraini (Yayasan Sembilan Pemuda Indonesia, 2026)
The philosophy of education in Indonesia reflects a conceptual foundation rooted in the cultural values, ethics, and thought heritage of Ki Hajar Dewantara, as well as the principles of Pancasila. However, academic literature on the philosophy of education remains scattered and has not been systematically mapped. This study aims to identify and analyze key themes emerging in the discourse on the philosophy of education in Indonesia through a Systematic Literature Review (SLR). This study follows the PRISMA 2020 protocol by examining 15 scientific articles published between 2020 and 2024, obtained from indexed national and international databases. The analysis shows that dominant themes in the literature include character education, strengthening Pancasila values, integrating local wisdom, the moral and spiritual dimensions of education, and the application of humanism and pragmatism in the context of modern education. These findings indicate that the discourse on the philosophy of education in Indonesia is evolving toward a more contextual, value-oriented, and responsive direction to national social and cultural challenges, rather than simply following classical philosophical schools of thought such as idealism or realism. This research contributes to providing a conceptual map of the direction of development of educational philosophy studies in Indonesia and offers a basis for strengthening philosophical reflection that is relevant to the needs of contemporary education.